Fluorescent zinc(ii)-based metal–organic frameworks for nitroaromatics sensing. (7th March 2018) - Ma, Yujie; Xu, Guanhong; Wei, Fangdi; Cen, Yao; Song, Yueyue; Shi, Menglan; Xu, Xiaoman; Sohail, Muhammad; Hu, Qin
Abstract : A new structural metal–organic framework with fluorescence properties was synthesized and applied for sensitive and selective sensing of nitroaromatics. Abstract : A new structural metal–organic framework with fluorescence properties, namely Zn4 (BTC)2 (OH)2 (CH3 OH)6 (NJMU-001), was synthesized by using 1, 3, 5-benzenetricarboxylic acid (H3 BTC) and zinc nitrate through a solvothermal reaction. In order to obtain good single crystals of NJMU-001, the factors affecting the reaction, such as the reaction temperature, reaction time, solvent and metal salt/ligand molar ratios, were studied. The phase purity of NJMU-001 was investigated via powder X-ray diffraction analysis, elemental analysis and FT-IR spectroscopy. Gas sorption measurements revealed that NJMU-001 was microporous and thermogravimetric analysis indicated that it was thermally stable under 200 °C. Fluorescence study of NJMU-001 in an N, N -dimethylformamide medium showed blue emission at 435 nm upon excitation at 370 nm. This emissive property was used for sensitive sensing of toxic and explosive nitroaromatics by exhibiting fluorescence quenching.